আনোয়ারউল্লাহ চৌধুরী : সংবর্ধনা গ্রন্থ - রহমান, সাঈদ-উর (ঢাকা : অনন্যা, 2020)
Contributed articles on Anwarullah Chowdhury, college teacher and educator from Bangladesh; commemorative volume.
Donated By Akbar Ali Khan
In Bengali.
Keywords: চৌধুরী, আনোয়ারউল্লাহ; College teachers -- Bangladesh -- Biography; Educators -- Bangladesh -- Biography